Inequalities theory of majorization and its applications - Marshall, Albert W. (Springer series in statistics., 2011)
Statisticians, probabilists, and mathematicians will all be interested in a expanded version of this classic work on inequalities. The theory of inequalities has applications in virtually every branch of mathematics.